5(-4)-6-7(-4)=2

Simple and best practice solution for 5(-4)-6-7(-4)=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(-4)-6-7(-4)=2 equation:


Simplifying
5(-4) + -6 + -7(-4) = 2

Multiply 5 * -4
-20 + -6 + -7(-4) = 2

Multiply -7 * -4
-20 + -6 + 28 = 2

Combine like terms: -20 + -6 = -26
-26 + 28 = 2

Combine like terms: -26 + 28 = 2
2 = 2

Add '-2' to each side of the equation.
2 + -2 = 2 + -2

Combine like terms: 2 + -2 = 0
0 = 2 + -2

Combine like terms: 2 + -2 = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| -7+-10P*2+-9(-10P*2+1)= | | (3y+100)+(y+80)=180 | | -5-15+1=14y-32-y | | -5x-2-10=2-(-2+4) | | 75-2x=-15 | | 16+2f=22 | | 2b+4=b-3 | | 20b^2-136b-28= | | (3/4)x=(5/8) | | 4(5x-7)=56 | | X+1+1=6x-5x+2 | | .40x+.1=.60 | | N=-300+15N | | 5a+2+2a-7+4a=7 | | 6z+19=4z+19 | | -5x-2-10=2-(x+4) | | 85l=685 | | 3(X+1)=2X+24-X | | -3(y-7+3)+3=0 | | 6g+4(g)=1-g | | -x+x=91+7 | | X=-7y-10 | | -2x-6=-2x-4 | | 2.39=x-40 | | 10+9C+5C*2-4+6C= | | a-2-2+15=1+3a | | 49h+20=314 | | -2x-6=-2-4 | | 4p+2+2p+1=8 | | -5x+9=17-x | | 6y=8x-10 | | 10t^2=12t+23 |

Equations solver categories